EFFICACY OF BASIL LEAF EXTRACT (OCIMUM Spp.) AGAINST MICROBES THAT CAUSES DENTAL AND ORAL DISEASES: A LITERATURE REVIEW - Muhammad Vegisa Nusantara; Ratna Sulistyorini; Maya Dian Rakhmawatie (Universitas Muhammadiyah Semarang, 2024)
Background: Infection is one of the most common dental and oral health problems experienced by the community. Most infections in the oral cavity are caused by Candida albicans and bacteria such as Streptococcus mutans. Currently, there is a tendency to use natural ingredients that are believed to be antifungal and antibacterial as a substitute for chemicals. One of the natural ingredients that have the potential as antifungal and antibacterial that is easily obtained by the community is basil leaves (Ocimum spp.). Objective: This study aims to determine the efficacy of basil leaf extract (Ocimum spp.) on the growth of C. albicans and S. mutans in vitro. Methods: A systematic literature review study using the Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) method was conducted to find scientific evidence of the efficacy of basil leaves (Ocimum spp). Result: Extracts from the majority of basil leaf species (Ocimum spp.) contain flavonoids, alkaloids, saponins, tannins, steroids, triterpenoids, which are expected to have activity as antifungal and antibacterial agents. The minimum inhibitory concentration (MIC) of basil leaf extract from various species, solvents and extraction methods varied with a range of 0.0025 – 25% w/v. Conclusion: The most effective basil leaf species in inhibiting the growth of C. albicans was Ocimum basilicum which was extracted using maceration method with methanol solvent (MIC 0.01%). Meanwhile, the most effective basil leaf species in inhibiting the growth of S. mutans was Ocimum sanctum L. which was extracted using the soxhletation method with 96% ethanol solvent (MIC 0.0025%).